Memprediksi Potensi Kebangkrutan Dengan Metode Fullmer H-Score Pada Usaha Mikro Kecil dan Menengah - Muh Fuad Alamsyah; Wiwin L. Husin; Zulkarnain I. Idris (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
This research was conducted on water hyacinth woven craft SMEs in the city of Gorontalo. This study aims to further analyze the performance of water hyacinth SMEs in the city of Gorontalo, especially their financial performance in maintaining their existence and how much effort SMEs make to minimize the potential for bankruptcy that will occur. The analytical method used is descriptive quantitative by calculating and analyzing bankruptcy ratio items consisting of 9 (nine) measurement indicators from the Fullmer H-Score method such as total assets, sales, returns, income, total debt, working capital, gross profit. , interest and cash flow (cash flow). The sample in this study amounted to 10 MSME actors. Based on the results of this study, it was found that all water hyacinth MSME actors in the city of Gorontalo, totaling 10 (ten) MSMEs were all in the HEALTHY category according to the measurement results of the Fullmer H-Score method.